Stock Return Problems In The Coal Sector: A Case Study Of The Use Of Price Earning Ratio And Firm Size Moderation - Sunaryo, Deni (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This research aims to find out the effect of Return On Asset, Current Ratio, Average Collection Period on Stock Returns with Price Earning Ratio and Firm Size as moderated variables. This research is on Coal Sub-Sector companies listed on the Southeast Asian Stock Exchange for the period 2012-2020. The data used is secondary data from the annual report. This research is quantitative research. The object used is a coal sub-sector company in Southeast Asia for the period 2012-2020. The data collected is secondary data with documentation methods in the form of annual company reports. The sampling method used in this study using purposive sampling techniques was obtained by 10 companies that presented complete financial statements, so that as many as 90 samples were obtained. The analytical techniques used are descriptive statistical analysis, moderated regression analysis (MRA), multiple linear regression, t test, f test, and determination coefficient test. Based on the discussion of the research results that have been described, it can be concluded that the Return On Assets, Current Ratio and Average Collection Period Simultaneously no significant effect on Stock Return. Price Earning Ratio (PER) moderate Return On Assets to Stock Return. While the Price Earning Ratio (PER) does not moderate the Current Ratio, Average Collection Period on Stock Return. Firm Size does not moderate Return On Assets Current Ratio Average Collection Period to Stock Return in the Coal Subsector listed on the Southeast Asian Stock Exchange for the 2012-2020 periods